The Development of Students’ Worksheet Based on the Context of the Lumajang Central Park to Teach Geometric Transformation Material - Asyifa, Rindu; Suwarno, Suwarno (Kreano, Jurnal Matematika Kreatif-Inovatif, 2024)
The use of Worksheet teaching materials and textbooks from the government at MTs Darul Ulum Ranupakis and learning methods that are still teacher-centered. The lack of involvement in the context around students has resulted in a lack of student interest in learning mathematics, especially in class IX. One alternative to overcome this is to develop contextually based Students’ Worksheet with the object of the Lumajang Central Park building. This Research aims to develop a teaching material design in the form of a Students’ Worksheet on geometric transformations based on the context of the Lumajang Central Park  Building that is valid, practical, and effective. This type of Research is Research and Development by following the ADDIE development model procedure with the stages of Analysis, Design, Development, Implementation, and Evaluation. This Research uses data collection techniques: observation, documentation, interviews, and questionnaires. The subjects in this Research were class IX students at MTs Darul Ulum Ranupakis. The results of the Research show that teaching materials in the form of geometric transformation worksheets based on the context of the Lumajang Regency Square building meet the criteria of valid, practical, and effective with percentages of 94.43% (very valid), 84.3% (very practical ) and 80% respectively (Good). These results show that the geometric transformation of Students’ Worksheet in the context of the Lumajang Central Park building is suitable for learning. This Research can be a reference and open up opportunities for future researchers to integrate contextual approaches to mathematics material and develop local context-based teaching materials or explore more innovative learning methods to attract interest in learning mathematics, especially class IX students. Penggunaan bahan ajar LKS dan buku paket dari pemerintah di MTs Darul Ulum Ranupakis dan metode pembelajaran yang masih berpusat pada guru serta kurangnya melibatkan konteks disekitar siswa membuat kurangnya minat peserta didik dalam belajar matematika, khususnya kelas IX. Salah satu alternatif untuk menanggulangi hal itu ialah mengembangkan LKPD berbasis kontekstual dengan objek bangunan alun-alun Kabupaten Lumajang. Penelitian ini bertujuan untuk mengembangkan desain bahan ajar berupa Lembar Kerja Peserta Didik (LKPD) transformasi geometri berbasis konteks bangunan alun-alun Kabupaten Lumajang yang valid, praktis dan efektif. Jenis penelitian ini yaitu Research and Development dengan mengikuti prosedur model pengembangan ADDIE dengan tahapan Analysis, Design, Development, Implementation, dan Evaluation. Teknik pengumpulan data yang digunakan dalam penelitian ini berupa observasi, dokumentasi, wawancara dan angket. Subjek dalam penelitian ini adalah siswa kelas IX MTs Darul Ulum Ranupakis. Hasil dari penelitian menunjukkan bahwa bahan ajar berupa LKPD transformasi geometri berbasis konteks bangunan alun-alun Kabupaten Lumajang memenuhi kriteria valid, praktis dan efektif dengan persentase masing-masing 94,43% (sangat valid), 84,3% (sangat praktis) dan 80% (baik). Melalui hasil tersebut dapat disimpulkan bahwa LKPD transformasi geometri dengan konteks bangunan alun-alun Kabupaten Lumajang layak untuk digunakan dalam pembelajaran. Penelitian ini dapat menjadi referensi dan membuka peluang untuk peneliti selanjutnya dalam mengintegrasikan pendekatan kontekstual pada materi matematika serta mengembangkan bahan ajar berbasis konteks lokal atau eksplorasi metode pembelajaran yang lebih inovatif untuk menarik minat belajar matematika terutama peserta didik kelas IX.